2013
DOI: 10.1111/lre.12028
|View full text |Cite
|
Sign up to set email alerts
|

Spatio‐temporal variation of gross CO2 and CH4 diffusive emissions from Australian reservoirs and natural aquatic ecosystems, and estimation of net reservoir emissions

Abstract: Carbon dioxide (CO 2 ) and methane (CH 4 ) diffusive emissions were measured during two field surveys in Queensland and Tasmania, Australia, using the floating chamber method. Bubbling and degassing emissions in 2010 were estimated in Koombooloomba Dam reservoir using only inverted funnels and gas concentrations, respectively. A total of 14 reservoirs and 16 rivers and lakes were sampled from 2006 to 2010. Spatial variation was substantial within each water body, as well as between them. The main drivers of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Fewer studies conducted worldwide have analysed the contribution of N 2 O to GHG emissions from reservoirs (Guerin et al, 2008;Mengis et al, 1997;Tremblay et al, 2005) despite N 2 O having a higher GWP than CH 4 . There are currently only two studies (Bastien and Demarty, 2013;Grinham et al, 2011) reporting CH 4 emissions and none for N 2 O from reservoirs in Australia -a country with over 2300 reservoirs covering a surface area in excess of 5700 km 2 at full supply (Geoscience Australia, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fewer studies conducted worldwide have analysed the contribution of N 2 O to GHG emissions from reservoirs (Guerin et al, 2008;Mengis et al, 1997;Tremblay et al, 2005) despite N 2 O having a higher GWP than CH 4 . There are currently only two studies (Bastien and Demarty, 2013;Grinham et al, 2011) reporting CH 4 emissions and none for N 2 O from reservoirs in Australia -a country with over 2300 reservoirs covering a surface area in excess of 5700 km 2 at full supply (Geoscience Australia, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…These reservoirs enable storage and greater certainty of supply compared to river and groundwater sources in Australia. In reservoirs without continuous water release, the primary CH 4 emission pathways to the atmosphere are ebullition from sediments, diffusion over the water-air interface and plant-mediated transport from littoral zones (Bastviken et al, 2004). Ebullition has been shown to be the dominant CH 4 emission pathway in many tropical systems (DelSontro et al, 2011;Devol et al, 1988;Grinham et al, 2011;Joyce and Jewell, 2003;Keller and Stallard, 1994;Soumis et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3). Given the very small isotopic fractionation (0.9992) of CH 4 during gas evasion (Knox et al, 1992), the only process that can explain the observed δ 13 CH 4 increase is CH 4 oxidation (Bastviken et al, 2002;Thottathil et al, 2018). We estimated that riverine CH 4 oxidation ranged from 0.38 to 1.80 mmol m −2 d −1 (expressed per squared metre of reservoir area for comparison), transforming 18 % to 32 % (depending on the sampling campaign) of the CH 4 to CO 2 within the first 19 km of the outflow.…”
Section: Degassing and Downstream Emissionsmentioning
confidence: 99%
“…While diffusion is the most frequently sampled, it is often not the main emission pathway (Demarty and Bastien, 2011). Indeed, measured ebullition, degassing, and downstream emissions range from negligible to several order of magnitude higher than diffusion in different reservoirs (Bastien and Demarty, 2013;DelSontro et al, 2010;Galy-Lacaux et al, 1997;Keller and Stallard, 1994;Kemenes et al, 2007;Teodoru et al, 2012;Venkiteswaran et al, 2013), making it a challenge to model total reservoirs GHG emissions.…”
mentioning
confidence: 99%